2019
DOI: 10.1088/1752-7163/ab0bee
|View full text |Cite
|
Sign up to set email alerts
|

The potential of breath analysis to improve outcome for patients with lung cancer

Abstract: Lung cancer remains the most common cause of cancer related death in both the UK and USA. Development of diagnostic approaches that have the ability to detect lung cancer early are a research priority with potential to improve survival. Analysis of exhaled breath metabolites, or volatile organic compounds (VOCs) is an area of considerable interest as it could fulfil such requirements. Numerous studies have shown that VOC profiles are different in the breath of patients with lung cancer compared to healthy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 164 publications
0
30
0
Order By: Relevance
“…Metabolites and VOCs have been investigated in lung cancer on exhaled breath [38][39][40] and urine [41,42]. Therefore, low weight molecules have been proposed as biomarkers of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites and VOCs have been investigated in lung cancer on exhaled breath [38][39][40] and urine [41,42]. Therefore, low weight molecules have been proposed as biomarkers of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The p-cresol exhibits cytotoxicity and genotoxicity and reduces endothelial barrier function in vitro [52,53]. P-cresyl sulfate, a sulfate-conjugate of p-cresol, suppresses Th1-type cellular immune responses in mice [39,42]. High levels of this metabolite in urine have been found in patients with cardiovascular and renal diseases [51].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that electronic nose technology based on pattern recognition of VOCs or identifying VOCs with gas chromatography/mass spectrometry can differentiate between subjects with and without lung cancer [13,14,17,20,[27][28][29]. Several studies using techniques for VOC identification have used logistic regression analysis to identify lung cancer-specific VOCs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of VOCs related with tumor metabolism show a promising future in the screening and diagnosis of several cancers [34]. Possible mechanisms of cancer-related VOC emissions include (1) persistent oxidative stress-induced lipid peroxidation of polyunsaturated fatty acids (PUFAs) (i.e., emission of alkanes, alkenes and aldehydes following cell-and mitochondrialmembrane perturbations by ROS attacks) (2) induction of cytochrome p-450 enzymes by environmental carcinogens and ROS molecules (3) overexpression of cytochrome p-450 enzymes in several tumor types, such as breast tumors, (4) cancer cell metabolism shift from oxidative phosphorylation to aerobic glycolysis, (5) molecular alterations in oncogenes and tumor suppressor genes [34,[38][39][40][41].…”
Section: Exhaled Breath Compositionmentioning
confidence: 99%
“…Of these identified compounds, many studies reported lipid peroxidation (i.e., decane, heptanal, octane, undecane) and mevalonate (i.e., isoprene) pathways, related ones being high in lung cancer compared to healthy controls [41][42][43]. Moreover, it has been suggested that [41] peroxidation processes may produce cancer-specific VOCs given the hypothesis that lung cancer cells present altered phospholipid profiles compared to that of healthy cells [44]. However, none of these markers have been translated into clinical practice yet.…”
Section: Exhaled Breath Compositionmentioning
confidence: 99%